Efeito neuroprotetor da lectina de Canavalia ensiformis (ConA) via sítio de ligação a aminoácidos em células da linhagem PC12 Adh - Roma, Renato Rodrigues (2025)
Glutamate, the main excitatory neurotransmitter in the central nervous system, plays a crucial role in various physiological functions. However, excess glutamate in the synaptic cleft induces excitotoxicity, a process associated with several neuropathological diseases and conditions. The search for drugs from bioactive plant compounds, such as lectins, becomes essential for human well-being. Lectins, proteins that specifically and reversibly bind to carbohydrates and glycoconjugates, demonstrate promising activities in the central nervous system, such as antioxidant, anti-inflammatory, and neuroprotective effects. However, their neuroprotective mechanisms focus only on the carbohydrate-recognition domain, neglecting other binding sites. Therefore, this study investigated the in vitro neuroprotective effect of Canavalia ensiformis lectin - ConA in PC12 cells and its in silico interaction with glutamate through a site different from the carbohydrate-recognition domain. ConA was tested for neuroprotection against glutamate-induced toxicity in PC12 cells using MTT assays. Fluorescence spectroscopy and molecular docking techniques were used to evaluate the interaction and affinity between ConA and glutamate. The results revealed that the neuroprotective effect of ConA is not dose- dependent and is independent of its carbohydrate-recognition domain. The mechanism of action discovered involves the direct sequestration of glutamate through ConA's amino acid binding site. Spectroscopy and molecular docking analyses confirmed this interaction through this hydrophobic site. These findings expand the therapeutic potential of plant lectins in the treatment of central nervous system diseases, opening new perspectives for the development of more targeted and innovative therapies.